(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2024)
On the basis of the Roman epigraphical sources of Hispania, this researching work studies in detail a few singular cases of individuals bearing maternal filiations. It develops a critical analysis of the possible anthroponymic and social circumstances which can explain this peculiar behaviour in a general context of paternal filiations. Three explanatory proposals are contrasted: the birth of the bearer of the maternal filiation outside of a legitimate marriage, the possible servile condition of this and the mother, and, finally, family and socio-cultural reasons in the bearer’s environment, such as fatherlessness, or a special pre-eminence of women in the family structures of certain communities, due to local traditions of pre-Roman origin.